Porous fiber aerogels and methods of making and use in protein adsorption separations

CN119613822BActive Publication Date: 2026-10-30WUHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411491451.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2026-10-30
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

为了解决现有的蛋白质分离纯化效率低成本高的问题,本发明提供一种多孔纤维气凝胶及制备方法和在蛋白质分离纯化中的用途

Benefits of technology

[0040](1)本发明所提供的多孔纤维气凝胶充分利用自身组分,构筑物均含有丰富的羟基官能团,暴露位点即蛋白质吸附位点,极大提高蛋白质吸附能力。还可以用来吸附带电荷的毒素,从而可以用来去除毒素。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613822B_ABST
    Figure CN119613822B_ABST
Patent Text Reader

Abstract

The application provides a porous fiber aerogel, a preparation method and application in protein adsorption and separation. The porous fiber aerogel comprises alginic acid fibers and sodium alginate, the alginic acid fibers and the sodium alginate are mixed, then are directionally frozen into shape by liquid nitrogen, and are crosslinked by calcium ions to form a regular vertical pore structure. The provided porous fiber aerogel has a high specific surface area, a large number of carboxyl functional groups on the surface, can combine a large number of positively charged proteins through electrostatic action and functional group action, is used for adsorption and separation of proteins, and has a good adsorption effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of protein separation and purification, specifically relating to a porous fiber aerogel, its preparation method, and its use in protein separation and purification. Background Technology

[0002] Protein products are in high demand in the food industry, life science research, and biopharmaceutical fields. In their production process, separation and purification are the most critical steps, determining the purity and bioactivity of the protein product and accounting for over 80% of the production cost. Therefore, efficient and cost-effective separation and purification technologies are key to the development of many industries.

[0003] Currently, commonly used protein separation and purification methods in engineering, such as precipitation, centrifugation, extraction, electrophoresis, and membrane separation, are either expensive, have low separation accuracy, or are prone to contamination, making them less than ideal extraction methods. Extensive research currently focuses on adsorption separation methods to achieve efficient, universal, and sustainable protein separation. However, research on protein adsorption separation materials still faces significant developmental bottlenecks. This is mainly because the widely used micron-sized protein adsorption separation media have large sizes (20-200 μm) and small pore sizes (<100 nm), leading to slow protein mass transfer, low throughput, high resistance, and high energy consumption. Therefore, designing protein adsorption separation materials with high adsorption capacity, high throughput, and low pressure drop is currently a key focus and hot topic in the field of protein separation and purification.

[0004] Alginic acid (ALA) is a natural polysaccharide derived from marine brown algae, composed of β-D-mannuronic acid and α-L-guluronic acid. Due to its wide availability and the abundance of active functional groups such as hydroxyl and carboxyl groups in its molecular chain, especially its strong negative surface charge, it provides abundant binding sites for positively charged proteins such as lysozyme, exhibiting excellent protein adsorption and separation potential. Alginic acid can form a stable "egg-box" structure gel in the presence of divalent cations such as calcium, but this structure suffers from dense density, lack of pores, small specific surface area, and limited adsorption sites. Combining or cross-linking with other materials such as cellulose fibers, chitosan, silk fibroin, and polyethylene glycol is an effective method for controlling the pore structure of alginate adsorbents; however, these materials, when combined with alginate, occupy some of its adsorption sites, significantly reducing the adsorption capacity of alginate itself. Therefore, the urgent task is to develop an alternative pore structure engineering strategy to fully expose the protein adsorption sites on the surface of alginate gels while avoiding the occupation of these sites by other materials. Alginic acid fibers exhibit a high specific surface area due to their high aspect ratio, providing a wider range of sites for protein adsorption. Constructing composite gel materials by synergistically combining alginate fibers and alginate gels holds promise for opening new avenues for building high-performance protein adsorption and separation materials; however, no relevant methods have been reported to date. Summary of the Invention

[0005] This invention aims to at least partially address one of the technical problems in related technologies. To solve the problem of high cost and low efficiency in existing protein separation and purification methods, this invention provides a porous fiber aerogel, its preparation method, and its application in protein separation and purification. The provided porous fiber aerogel is constructed by cross-linking alginate fibers and sodium alginate with calcium ions. Both alginate fibers and sodium alginate contain a large number of hydroxyl functional groups, which can provide numerous adsorption sites for positively charged proteins, and further enhance the adsorption capacity for positively charged proteins through hydrogen bonding. Furthermore, the formed porous fiber aerogel also possesses a vertical pore network structure, which can reduce flow resistance, increase water treatment throughput, and avoid clogging problems. This achieves the goal of reducing protein production costs and improving protein production efficiency by constructing a low-cost yet high-performance protein adsorption and separation material.

[0006] Specifically, the present invention provides the following technical solution:

[0007] In a first aspect, the present invention provides a porous fiber aerogel comprising alginate fiber and sodium alginate, wherein the alginate fiber and sodium alginate are mixed and then orientedly frozen and molded by liquid nitrogen, and cross-linked by calcium ions to form a vertically uniform pore structure.

[0008] The provided porous fiber aerogel comprises cellulose alginate and sodium alginate, with cellulose alginate serving as the scaffold and sodium alginate as the binder. The two are directionally frozen with liquid nitrogen to form a vertically uniform pore structure with abundant pores distributed on both the inner and outer walls, resulting in a high specific surface area. Its surface contains numerous carboxyl functional groups, which can bind a large number of positively charged proteins through electrostatic and functional group interactions. Placing the porous fiber aerogel in a protein mixture solution to be purified allows for the effective adsorption of positively charged proteins into the porous fiber aerogel, achieving protein separation and purification.

[0009] According to embodiments of the present invention, the provided porous fiber aerogel may further include the following technical features:

[0010] In some embodiments of the present invention, the mass ratio of the alginate fiber to the sodium alginate is 2.5–10:97.5–90. According to a preferred embodiment, the mass ratio of the alginate fiber to the sodium alginate is 5:95.

[0011] In some embodiments of the present invention, the alginate fiber is prepared by wet spinning.

[0012] A second aspect of the present invention provides a method for preparing porous fiber aerogels, comprising:

[0013] A cellulose alginate solution and a sodium alginate solution are provided. The cellulose alginate solution is uniformly dispersed in the sodium alginate solution to obtain a precursor solution.

[0014] The precursor solution is subjected to a first freezing and a first vacuum drying process to obtain an uncrosslinked aerogel;

[0015] The uncrosslinked aerogel was crosslinked with calcium ions, followed by a second freezing and a second vacuum drying process to obtain the porous fiber aerogel.

[0016] The provided porous fiber aerogel is bonded with alginate fiber and sodium alginate, resulting in a more stable structure. It is then prepared by liquid nitrogen directional freezing to form a vertically uniform pore structure, which facilitates the flow of the liquid to be treated, increases the processing throughput, reduces the processing pressure drop, and improves the efficiency of protein separation and purification.

[0017] According to embodiments of the present invention, the preparation method of the porous fiber aerogel described above may further include the following technical features:

[0018] In some embodiments of the present invention, the mass concentration of the alginate cellulose solution is 0.5 wt% to 5 wt%.

[0019] The concentration of the sodium alginate solution is 0.5 wt% to 5 wt%.

[0020] The calcium ions are a calcium chloride solution with a concentration of 0.2 mol / L to 0.5 mol / L.

[0021] In some embodiments of the present invention, the first vacuum drying process and the second vacuum drying process are each independently selected from vacuum drying processes performed at a pressure of less than 30 Pa.

[0022] In some embodiments of the present invention, the first freezing is a liquid nitrogen directional freezing process. The temperature for the liquid nitrogen directional freezing process is approximately -190 degrees Celsius.

[0023] In some embodiments of the present invention, the second freezing is performed at a temperature of -20 to -60 degrees Celsius. A refrigerator can be used for this freezing process.

[0024] The third aspect of the present invention provides the application of the porous fiber aerogel described in the first aspect or the porous fiber aerogel obtained according to the preparation method described in the second aspect in the field of protein adsorption and separation or toxin separation.

[0025] A fourth aspect of the present invention provides a method for separating a target protein from a sample, comprising:

[0026] Porous fiber aerogel is added to the sample for adsorption treatment, wherein the porous fiber aerogel is the porous fiber aerogel described in the first aspect or the porous fiber aerogel obtained according to the preparation method described in the second aspect.

[0027] The target protein was isolated from the sample.

[0028] In some embodiments of the present invention, the target protein is selected from at least one of lysozyme, hemoglobin, whey protein, cytochrome C, bromelain, and papain.

[0029] A fifth aspect of the present invention provides a method for purifying a target protein, comprising:

[0030] A porous fiber aerogel is added to a sample containing the target protein for adsorption treatment. The porous fiber aerogel is the porous fiber aerogel described in any one of the first aspects or the porous fiber aerogel obtained according to the preparation method described in any one of the second aspects.

[0031] Impurities in the sample containing the target protein are separated and removed to obtain a porous fiber aerogel adsorbed with the target protein.

[0032] The porous fiber aerogel adsorbed with the target protein is subjected to desorption treatment to obtain the target protein.

[0033] The sample containing the target protein mentioned is an acidic sample solution, for example, with a pH value of 2 to 6.5, preferably 3 to 4. According to an embodiment of the present invention, during the desorption process, a calcium chloride solution can be used as the eluent. The porous fiber aerogel containing the target protein is placed in the eluent and shaken to perform the desorption process. Specifically, the eluent used can be a 0.1M to 0.2M calcium chloride solution. Shaking can be performed on a shaker, for example, at a speed of 100 to 200 rpm (e.g., 150 rpm). Then, by adjusting the pH to reach the isoelectric point of the target protein, the target protein precipitates, and the target protein is separated and obtained.

[0034] According to an embodiment of the present invention, the target protein carries a positive charge.

[0035] A sixth aspect of the present invention provides a method for removing toxins from a sample, comprising:

[0036] A porous fiber aerogel is added to a sample containing toxins for adsorption treatment to obtain a porous fiber aerogel that adsorbs toxins; the porous fiber aerogel is the porous fiber aerogel described in any one of the first aspects or the porous fiber aerogel obtained according to the preparation method described in any one of the second aspects.

[0037] Separate and remove adsorbed toxins from porous fiber aerogels.

[0038] The toxins mentioned carry a positive charge and include, but are not limited to, urea, uric acid, and creatinine.

[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0040] (1) The porous fiber aerogel provided by this invention makes full use of its own components. The structures all contain abundant hydroxyl functional groups, and the exposed sites are protein adsorption sites, which greatly improves the protein adsorption capacity. It can also be used to adsorb charged toxins, thereby removing toxins.

[0041] (2) The provided aerogel has a vertically uniform pore structure, which increases the liquid flow through the aerogel. In addition, a large number of pore structures are distributed on the wall surface, which greatly increases the specific surface area and improves the protein adsorption capacity.

[0042] (3) The raw materials required for the preparation of aerogels are abundant and inexpensive. The preparation method is simple and does not require expensive equipment. The preparation process is safe and pollution-free. This technology has a low barrier to entry, good results, and can be used in a wide range of protein separation and purification processes, saving protein production costs and improving protein production efficiency. Attached Figure Description

[0043] Figure 1 This is a schematic diagram of the preparation process of porous fiber aerogel according to an embodiment of the present invention.

[0044] Figure 2 The adsorption capacity of different porous fiber aerogels provided according to embodiments of the present invention.

[0045] Figure 3 The graph shows the effect of the amount of porous fiber aerogel added according to an embodiment of the present invention on the adsorption capacity.

[0046] Figure 4 The effect of porous fiber aerogel provided according to embodiments of the present invention on the adsorption of proteins in solutions with different pH values.

[0047] Figure 5 The results show the change in adsorption capacity of porous fiber aerogels as the lysozyme concentration increases, according to an embodiment of the present invention.

[0048] Figure 6 The adsorption kinetics results of the porous fiber aerogel adsorption capacity over time provided according to an embodiment of the present invention are shown.

[0049] Figure 7The effect of porous fiber aerogel provided according to embodiments of the present invention on the protein adsorption capacity after different cycles.

[0050] Figure 8 The results of scanning electron microscopy observations of porous fiber aerogels provided according to embodiments of the present invention are shown.

[0051] Figure 9 These are porous fiber aerogels of different shapes and sizes prepared according to embodiments of the present invention.

[0052] Figure 10 The results are the total lysozyme content provided in different eluents according to embodiments of the present invention.

[0053] Figure 11 This is an electrophoresis result diagram provided according to an embodiment of the present invention. Detailed Implementation

[0054] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.

[0055] This invention provides a porous fiber aerogel, which is mainly composed of alginate cellulose and sodium alginate as raw materials. The alginate cellulose is bonded together with sodium alginate solution, resulting in a more stable structure. It is then directionally frozen and shaped using liquid nitrogen, and after calcium ion cross-linking and freezing, a vertically uniform pore structure is formed. When the provided porous fiber aerogel is placed in a protein mixture solution to be purified, positively charged proteins can be effectively adsorbed into the porous fiber aerogel, thereby achieving protein separation and purification.

[0056] During our research, we attempted to prepare porous fiber aerogels using a variety of raw materials, but the results were unsatisfactory. For example, using cellulose acetate and sodium alginate as raw materials to prepare porous fiber aerogels resulted in poor adsorption performance, with an adsorption capacity of only about 70 mg / g. Porous fiber aerogels composed of alginate-based materials possess abundant surface carboxyl active sites and, combined with hydrogen bonding, exhibit ultra-high adsorption capacity for positively charged proteins. Combined with the high specific surface area of ​​the fibers, this significantly increases the number of protein adsorption sites, resulting in an ultra-high protein adsorption capacity exceeding 8.35 g / g.

[0057] Wet spinning is a spinning method in which fiber-forming polymers are dissolved in a suitable solvent to prepare a solution with a certain viscosity and good spinnability. The solution is then extruded through a spinneret to form a fine stream, which enters a coagulation bath to form fibers. The alginate fiber used is obtained through wet spinning. To obtain alginate fiber through wet spinning, a sodium alginate solution is placed in a syringe and extruded through a spinneret to form a fine stream. This stream enters a coagulation bath (usually a calcium chloride solution), where the sodium alginate reacts with calcium ions to form calcium alginate gel fibers. The coagulated fibers are then stretched to improve their strength and orientation. Residual coagulant and unreacted sodium alginate are washed away from the fibers. The wet fibers are then dried to obtain the final dry fibers. This alginate fiber can be commercially available or prepared in-house. The sodium alginate powder used is commercially available.

[0058] Different shapes can be prepared using liquid nitrogen directional cryogenic molding, forming porous fiber aerogels of various shapes to suit different applications.

[0059] The porous fiber aerogel provided by this invention has certain mechanical properties, can exist stably in fluids, and has certain compression and shape memory capabilities.

[0060] The provided porous fiber aerogel can be used to adsorb positively charged proteins or toxins under acidic conditions, thereby enabling the adsorption and separation of proteins or the separation and removal of toxins. The proteins mentioned include, but are not limited to, lysozyme, hemoglobin, whey protein, cytochrome C, bromelain, and papain, while the toxins mentioned include, but are not limited to, urea, uric acid, or creatinine.

[0061] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other. Many specific details are set forth in the following description to provide a thorough understanding of the present invention; however, the present invention may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present invention is not limited to the specific embodiments disclosed below.

[0062] Unless otherwise specified, the alginate fiber used was commercially available wet-spun alginate fiber. Sodium alginate was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., calcium chloride from Sinopharm Group Pharmaceutical Co., Ltd., lysozyme from Shanghai Maclean Biochemical Technology Co., Ltd., and PBS buffer from Lanjieke Technology Co., Ltd. All aqueous solutions were prepared with deionized water (resistivity = 18.25 MΩ*cm).

[0063] Example 1

[0064] Example 1 prepared porous fiber aerogels with different proportions, including the following steps:

[0065] A 1 wt% alginate fiber solution was prepared and processed using a soymilk maker for 10 minutes to completely disperse the fiber. A 1 wt% sodium alginate solution was then prepared and mixed with the alginate fiber solution at different mass ratios to obtain a homogeneous precursor solution (reference). Figure 2 As shown, the mass fractions of alginate fiber are 0, 2.5%, 5%, 10%, 20%, 40%, 50%, 60%, 80%, 90%, and 100%, respectively.

[0066] The precursor solution was poured into a mold and directionally frozen with liquid nitrogen. The resulting frozen block was placed in a freeze dryer and vacuum dried under a pressure of less than 30 Pa to prepare an uncrosslinked aerogel.

[0067] The uncrosslinked aerogel was immersed in a 0.3M calcium chloride solution for 20 minutes, then rinsed repeatedly with pure water to remove residual calcium chloride from the surface of the aerogel. The aerogel was then placed in a -60°C freezer to freeze completely, and then placed in a freeze dryer for vacuum drying under a pressure of less than 30 Pa to finally prepare a crosslinked porous fiber aerogel.

[0068] Example 2

[0069] Example 2 tested the protein adsorption properties of porous fiber aerogels with different proportions prepared in Example 1.

[0070] Taking the porous fiber aerogels prepared by mixing sodium alginate solution and cellulose alginate solution in different proportions as described in Example 1 as an example, the protein adsorption performance of the aerogels was evaluated using lysozyme as a template protein.

[0071] The pH of a commercially available phosphate buffer solution was adjusted to 3 using hydrochloric acid and sodium hydroxide. Then, 200 mg of lysozyme was added to 100 ml of PBS buffer solution with slow stirring. 80 mg of porous fiber aerogel was immersed in an Erlenmeyer flask containing the lysozyme solution. After shaking at 150 rpm for a certain period, 2 ml of the solution sample was taken. The change in absorbance at 278 nm was measured using a UV-Vis spectrophotometer (Tsushima UV-1601PC) to determine the concentration of the lysozyme solution before and after adsorption. The lysozyme adsorption capacity of the porous fiber aerogel was calculated based on the concentration difference of the protein solution before and after adsorption.

[0072] The following formula is used to calculate the protein adsorption capacity of aerogels:

[0073] q e=V(C0-C) e ) / m

[0074] Where, q e V is the adsorption capacity at equilibrium, C0 and Ce are the initial and final concentrations of lysozyme at dynamic adsorption equilibrium, and m is the amount of adsorbent added.

[0075] Experimental results are as follows Figure 2 As shown, with the increase of the proportion of alginate cellulose solution in the aerogel preparation precursor solution, the protein adsorption performance of the resulting aerogel initially increases and then decreases, and after reaching a 5:5 ratio, it again shows a trend of initially increasing and then decreasing. It is noteworthy that under the condition of 80 mg porous fiber aerogel dosage, the protein adsorption performance is best when only 5% alginate cellulose is added, reaching 2.4 g / g. The interaction between fiber content and adsorption effect fully demonstrates the structure-activity relationship that the aerogel fiber structure determines the protein adsorption performance. Among these, the porous fiber aerogel prepared with a 5% mass fraction of alginate cellulose exhibits the best adsorption performance, and further research is conducted based on this.

[0076] Example 3

[0077] Example 3 investigated the effect of aerogel dosage (using the aerogel prepared with 5% alginate fiber as described in Example 2) on its maximum adsorption capacity in the same 100ml, 2mg / ml lysozyme solution with pH=3.

[0078] Experimental results are as follows Figure 3 As shown, the experimental results indicate that the protein adsorption performance of the porous fiber aerogel varies with the amount of aerogel added. When the added amount is greater than 20 mg, the adsorption capacity of the aerogel decreases with increasing added amount; when the added amount is less than 20 mg, the adsorption capacity of the aerogel increases with increasing added amount. The aerogel reaches its maximum adsorption capacity (8.35 g / g) at a added amount of 20 mg. This may be because when the added amount is greater than 20 mg, the adsorption sites on the aerogel surface are not fully occupied by lysozyme, thus failing to fully realize its adsorption potential. Conversely, when the added amount is less than 20 mg, there are insufficient adsorption sites, and lysozyme enzymes compete with each other, resulting in the failure to achieve optimal adsorption performance. Therefore, the following studies all use an aerogel added amount of 20 mg.

[0079] Example 4

[0080] Example 4 further investigated the effect of solution properties on protein adsorption in porous fiber aerogels.

[0081] The pH of a commercially available phosphate buffer solution was adjusted to between 2 and 8 using hydrochloric acid and sodium hydroxide. Lysozyme solutions of different concentrations (0-4 mg / ml) were prepared. Taking an aerogel containing 5% alginate cellulose as an example, which exhibits the best adsorption performance, the adsorption performance of the lysozyme was determined by referring to the above method.

[0082] Experimental results are as follows Figure 4 As shown, the experimental results indicate that the protein adsorption performance of the porous fiber aerogel increases with increasing solution pH in the pH range of 2-3, reaching a maximum of 8.35 g / g at pH 3, and then decreases with further increases in pH. However, it maintains relatively excellent protein adsorption performance within the solution pH range of 2-7, with an adsorption capacity remaining above 1.5 g / g.

[0083] like Figure 5 As shown, the adsorption capacity of the porous fiber aerogel increases with the increase of lysozyme concentration in the solution. The aerogel with an addition of 20 mg reaches adsorption equilibrium when the lysozyme concentration is 2 mg / ml.

[0084] Figure 6 The adsorption kinetics of aerogel adsorption amount over time are shown under the above-mentioned optimal conditions.

[0085] Example 5

[0086] Example 5 evaluated the recyclability of porous fiber aerogels.

[0087] The reusability of porous fiber aerogels was evaluated by conducting a 10-cycle protein adsorption-desorption experiment. First, adsorption experiments were performed using the optimal aerogel mentioned in Example 3 above. After sufficient adsorption time, the concentration of lysozyme solution after adsorption was measured. Then, using 0.1M calcium chloride solution as the eluent, the adsorbed aerogel was transferred to 50 ml of calcium chloride solution and placed in a shaker at 150 rpm for desorption. Every 10 minutes, the aerogel was transferred to a fresh calcium chloride solution, and the above operation was repeated until no lysozyme absorption peak was detected in the final eluent. The resulting aerogel was then rinsed five times with ultrapure water to remove residual calcium chloride and used for subsequent adsorption experiments. The desorbed aerogel was reused repeatedly in 10 cycles to measure its reusability.

[0088] Experimental results are as follows Figure 7 As shown, the experimental results indicate that after 5 cycles, the protein adsorption performance of the aerogel decreased by only ≤10%, and after 10 cycles, the protein adsorption performance decreased by only ≤15%. The protein adsorption capacity of the aerogel remained above 6.7 g / g, demonstrating excellent protein adsorption performance and good recyclability.

[0089] Example 6

[0090] Example 6 describes the structural characterization and mechanism investigation of the prepared porous fiber aerogel.

[0091] like Figure 8 As shown, the morphology of the aerogel, observed by scanning electron microscopy (SEM), reveals that the porous fiber aerogel obtained in this invention exhibits a 3D skeleton frame with a combination of large and small pores and a vertically uniform pore structure, possessing super-strong adsorption capacity. Furthermore, alginate fiber and sodium alginate powder are abundant, low-cost, biosafe, and readily available natural polymer materials, allowing for the continuous production of aerogels. The good controllability of the preparation process ensures the possibility of designing aerogels of different shapes and sizes, such as "W", "H", and "U" (e.g., ...). Figure 9 (As shown).

[0092] Zeta potential testing showed that, within a pH range of 2 to 8, both the raw materials, including cellulose alginate and sodium alginate powder, and the surface of the prepared aerogel carried a negative charge. In contrast, the isoelectric point of lysozyme is generally between pH 10.5 and 11.0, and it carries a positive charge at pH values ​​below 10.5. This indicates an electrostatic interaction between the aerogel and lysozyme, promoting the aerogel's adsorption performance of lysozyme.

[0093] The compression properties of the aerogel show that the optimal mechanical properties are achieved when the ratio of cellulose alginate to sodium alginate powder is 1:1. Furthermore, it maintains a certain shape during 1000 cycles of compression without completely collapsing. The aerogel also exhibits good shape memory in aqueous solutions; when kneaded into a ball and placed in an aqueous solution, it recovers its original shape after a short period.

[0094] Investigations into the adsorption kinetics mechanism of this aerogel revealed that its kinetic adsorption process for lysozyme exhibits a higher degree of fit with the quasi-second-order kinetic model, indicating that the adsorption of lysozyme between the aerogel involves not only physical interactions but also chemical reactions. Furthermore, its isothermal adsorption process better conforms to the Langmuir monolayer adsorption model, suggesting that uniform monolayer adsorption occurs, further demonstrating the abundance and readily accessible carboxyl functional groups within the aerogel.

[0095] Example 7

[0096] Example 7: Extraction of lysozyme from egg white using the porous fiber aerogel of the present invention.

[0097] Mix 50g of egg white stock solution with 200ml of phosphate buffer solution (pH=6), and centrifuge the resulting mixed egg white solution at 10000rpm for 15min to obtain a clear and transparent egg white solution free of insoluble impurities.

[0098] To further test the extraction ability of porous fiber aerogel for lysozyme from egg white, 60 mg of porous fiber aerogel was placed in 50 ml of treated egg white and continuously shaken at 150 rpm for 8 h at room temperature (25°C). The aerogel after lysozyme extraction was then removed from the egg white solution and rinsed alternately with pH 6 buffer and deionized water until no protein absorption peak was detected at 280 nm in the rinsing solution. Subsequently, the aerogel was immersed in 0.1 M calcium chloride solution and desorbed by shaking at 150 rpm. Each desorption cycle used 5 ml of solution and lasted 10 min.

[0099] Then, the lysozyme content in the eluent was detected at 280 nm using a UV spectrophotometer. Quantitative calculations showed that the total lysozyme content extracted from 10g of original egg white solution by the aerogel was 68.7mg (e.g., ...). Figure 10 (As shown).

[0100] Furthermore, the purity of the protein extract was qualitatively analyzed using SDS-PAGE. In SDS-PAGE electrophoresis, the lysozyme band typically appears at 14.7 kD. The egg white solution after aerogel adsorption did not show a lysozyme band at 14.7 kD, indicating that the lysozyme in the solution was fully adsorbed onto the aerogel. The eluent showed a lysozyme band at 14.7 kD, indicating that the lysozyme adsorbed on the aerogel was successfully eluted. Compared to the original egg white solution, the obtained protein eluent only showed one clear electrophoretic band at 14.7 kD, demonstrating that the alginate cellulose aerogel can effectively separate and purify lysozyme from egg white, exhibiting good practical application results (e.g., ...). Figure 11 (As shown).

[0101] Although embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions, and variations to the above embodiments within the scope of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A porous fiber aerogel, characterized in that, It includes alginate fiber and sodium alginate. The alginate fiber and sodium alginate are mixed and then shaped by liquid nitrogen directional freezing and cross-linked by calcium ions to form a vertical uniform pore structure. The mass ratio of the alginate fiber to the sodium alginate is 2.5~10:97.5~90.

2. The porous fiber aerogel according to claim 1, characterized in that, The alginate fiber is prepared by wet spinning.

3. A method for preparing the porous fiber aerogel according to any one of claims 1 to 2, characterized in that, include: A cellulose alginate solution and a sodium alginate solution are provided. The cellulose alginate solution is uniformly dispersed in the sodium alginate solution to obtain a precursor solution. The precursor solution is subjected to a first freezing and a first vacuum drying process to obtain an uncrosslinked aerogel; The uncrosslinked aerogel was crosslinked with calcium ions, followed by a second freezing and a second vacuum drying process to obtain the porous fiber aerogel.

4. The preparation method according to claim 3, characterized in that, The mass concentration of the alginate cellulose solution is 0.5wt%~5wt%; The sodium alginate solution has a mass concentration of 0.5 wt% to 5 wt%. The calcium ions are derived from a calcium chloride solution with a concentration of 0.2 mol / L to 0.5 mol / L.

5. The preparation method according to claim 3, characterized in that, The first vacuum drying process and the second vacuum drying process are each independently selected from vacuum drying processes performed at a pressure of less than 30 Pa.

6. The preparation method according to claim 3, characterized in that, The first freezing process is liquid nitrogen directional freezing.

7. The preparation method according to claim 3, characterized in that, The second freezing process involves freezing at a temperature of -20 to -60 degrees Celsius.

8. The application of the porous fiber aerogel according to any one of claims 1 to 2 or the porous fiber aerogel obtained by the preparation method according to any one of claims 3 to 7 in the field of protein adsorption and separation or toxin separation.

9. A method for separating a target protein from a sample, characterized in that, include: Porous fiber aerogel is added to the sample for adsorption treatment. The porous fiber aerogel is the porous fiber aerogel according to any one of claims 1 to 2 or the porous fiber aerogel obtained by the preparation method according to any one of claims 3 to 7. The target protein was isolated from the sample.

10. The method according to claim 9, characterized in that, The target protein is selected from at least one of lysozyme, hemoglobin, whey protein, cytochrome C, bromelain, and papain.

11. A method for purifying a target protein, characterized in that, include: Porous fiber aerogel is added to the sample containing the target protein for adsorption treatment. The porous fiber aerogel is the porous fiber aerogel according to any one of claims 1 to 2 or the porous fiber aerogel obtained by the preparation method according to any one of claims 3 to 7. Impurities in the sample containing the target protein are separated and removed to obtain a porous fiber aerogel adsorbed with the target protein. The porous fiber aerogel adsorbed with the target protein is subjected to desorption treatment to obtain the target protein.

12. The method according to claim 11, characterized in that, The target protein carries a positive charge.

13. A method for removing toxins from a sample, characterized in that, include: Porous fiber aerogel was added to a sample containing toxins for adsorption treatment to obtain a porous fiber aerogel that adsorbs toxins. The porous fiber aerogel is the porous fiber aerogel according to any one of claims 1 to 2 or the porous fiber aerogel obtained by the preparation method according to any one of claims 3 to 7; Separate and remove porous fiber aerogels that adsorb toxins.

14. The method according to claim 13, characterized in that, The toxin carries a positive charge.